Hidden and non measurable trade policies: the case of state controlled firms - Gianpaolo Rossini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2017)
A hot issue in trade negotiations concerns the existence of stateowned firms and state subsidies. Disputes between the US and the EU and the issue of the recognition of the status of a market economy to China are often the epitome of that. In Germany the giant Volkswagen is state controlled, in China almost 1/3 of firms are state controlled and loom in almost all industries often with relevant or even dominant market shares. State enterprises maximize home social welfare. When they export or compete with foreign producers at home their specific objective function make them a useful vehicle for disguised trade policies. We investigate trade cases with oligopoly and state or quasi state owned firms. Increasing returns to scale come into the picture in some instances. Dumping and foreclosure of the domestic market emerge explaining both the possibility of having home prices higher or lower than export prices. Possible counteracting policies can be devised and an example of a production subsidy is presented.
Keywords: F12; F13; L32; 330